Comparison of Higher Fashion Involvement Group and Lower Fashion Involvement Group in Taiwan - Huang, Yu-Chiao (2013)
Fashion collaboration becomes a common marketing strategy for many fashion brands in order to attract consumers’ attentions and stand out from competitors. The purpose of this dissertation is to explore the formation of consumers’ attitudes toward fashion collaboration. First, it intends to distinguish different types of consumers, which are higher fashion involvement and lower fashion involvement. Second, by utiliseing four different variables, which are prior attitudes, product fit, brand, and brand familiarity, to discuss how consumers’ attitudes are influenced by these variables.